A methodology of informatics: the role of methodology in improvement of theory - Voverienė, Ona (Knygotyra, 1990)
The article has a propounding character. Based on methodological literature, the essence of the concept "methodology" is revealed, explaining the role of scientific methods in knowledge and the role of methodology in improving theory and research work in some fields of knowledge. The results of the literature analysis are considered a starting point for investigating the methodology of informatics. Currently, there is no developed system of philosophical, scientific, and general-theoretical principles that determine the program and methods for investigating the theory and methodology of informatics. Additionally, there is no established theory of method and scientific approach to the objective evaluation of practice. The absence of methodology is a major cause and effect of the crisis in contemporary information theory. We can only discuss the methods used in research work in the field of informatics. Special methods in informatics—such as statistical analysis of scientific documents, statistical analysis of references, and the method of ranking—are characterized. The main laws of informatics are discovered using these methods. A definition of the methodology of informatics and its main aims is put forward for discussion.